2015
DOI: 10.3892/ijo.2015.2962
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 silencing inhibits tumor progression of mantle cell lymphoma and enhances chemosensitivity

Abstract: Abstract. B7-H3 (CD276), known as a member of B7 immunoregulatory family, is a type I transmembrane glycoprotein aberrantly expressed in numerous types of cancer and associated with poor prognosis. However, the role of B7-H3 in oncogenesis and chemosensitivity of mantle cell lymphoma (MCL) remains unknown. We determined the effects of downregulating B7-H3 expression on tumor progression and the sensitivity of chemotherapeutic drug in mantle cell lymphoma. B7-H3 knockdown was performed using lentivirus transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…The same phenomenon was observed in the cell invasion test. Silencing B7-H3 can impede cell migration and inhibit cell invasion via downregulating the expression of MMP-2 (13). Thus, we measured the invasion related proteins by western blotting and found that MMP-2 were lower in A2780-sh-B7-H3 and SKOV3-sh-B7-H3 cells than in the NC groups ( Fig.…”
Section: B7-h3 Expression In Relation To Patient Clinicopathologicalmentioning
confidence: 86%
“…The same phenomenon was observed in the cell invasion test. Silencing B7-H3 can impede cell migration and inhibit cell invasion via downregulating the expression of MMP-2 (13). Thus, we measured the invasion related proteins by western blotting and found that MMP-2 were lower in A2780-sh-B7-H3 and SKOV3-sh-B7-H3 cells than in the NC groups ( Fig.…”
Section: B7-h3 Expression In Relation To Patient Clinicopathologicalmentioning
confidence: 86%
“…And restoration of CD276 completely abrogated the tumor suppressor role of miR-187. The oncogenic activities of CD276 have been reported in many human cancers, including acute monocytic leukemia [30], non-small cell lung cancer [31], gastrointestinal carcinoma [15, 20, 32], and mantle cell lymphoma [33]. Despite the majority of studies on CD276 and cancer emphasize the paradox immunological role of CD276, several studies showed that CD276 can regulate tumor progression and chemosensitivity by targeting with signaling pathways involved in non-immunological systems.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found in another study that the treatment using the same plasmid of B7-H3 shRNA combined with other chemotherapy drugs dramatically inhibited the growth of mantle cell lymphoma Maver and Z138 xenografts by 92.3% and 92.9%, respectively. 27 Similarly, previous studies have also reported that B7-H3 may promote cancer resistance to drug treatments in breast cancer and pancreatic carcinoma xenograft models. 28,37 Although B7-H3 is a type I transmembrane protein, we find that its protein is also highly expressed in the nuclei and cytoplasm of AML M5 U937 cells, with a similar subcellular distribution as colorectal cancer, detected by immunohistochemical analysis.…”
Section: Figurementioning
confidence: 78%
“…In order to rule out unspecific effects, we used the same recombinant lentivirus-mediated B7-H3 knockdown in mantle cell lymphoma Maver and Z138 cell lines in another study, and also made the conclusion that B7-H3 promotes mantle cell lymphoma progression and that targeting B7-H3 knockdown significantly enhances the chemosensitivity in vitro and in vivo. 27 This indicates that B7-H3 promotes tumor progression in a series of hematologic malignancies, and that B7-H3 silencing enhances chemosensitivity, though not only in U937 cells. The strategy of targeting B7-H3 may provide a new therapeutic approach to hematologic malignancies, such as in AML M5.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation